Comparativo de seis variedades de Mani (Arachis Hypogaea L.) en fenología y rendimiento, en un suelo aluvial provincia de Moyobamba - Valle Del Alto Mayo - Guerrero Acha, Darwin (2009)
Design Under a randomized complete block with six treatments and three replications, which investigated the "phenology and yield of six varieties of peanut in the province of Moyobamba - Alto Mayo Valley," in order to select and determine the strain or varieties adapted to the area and more efficient. The parcel is located in the town of Tingana, at an altitude of 862 msnmm, an average temperature of 23 degrees C, and an average rainfall of 83.6 mm / month in an alluvial soil of silty loam texture. The varieties evaluated were purple, InfielIillo, White Tarapoto, Angelillo, Costeno Bagüiño; being assessed the following parameters: percentage of emergence, plant height, days to onset of flowering, days to peak flowering, pod yield per plant, number of seeds per pod, pod length, pod width, pod yield per hectare, seed yield per plant, seed length, seed width, weight of 100 seeds, dry grain yield per hectare. Concluding that the six varieties evaluated, varieties had better adaptation and performance in the Alto Mayo Valley was the variety with 2822.22 Dwelling Costeño kg / ha and 1973.33 kg / ha of dry grain.